2018
DOI: 10.1089/ast.2017.1666
|View full text |Cite
|
Sign up to set email alerts
|

Organic Haze as a Biosignature in Anoxic Earth-like Atmospheres

Abstract: Early Earth may have hosted a biologically mediated global organic haze during the Archean eon (3.8–2.5 billion years ago). This haze would have significantly impacted multiple aspects of our planet, including its potential for habitability and its spectral appearance. Here, we model worlds with Archean-like levels of carbon dioxide orbiting the ancient Sun and an M4V dwarf (GJ 876) and show that organic haze formation requires methane fluxes consistent with estimated Earth-like biological production rates. On… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 115 publications
(228 reference statements)
3
79
0
Order By: Relevance
“…The CO 2 content is similar to Earth's, f CO 2 = 3.6e-4, and the rest of the atmosphere consists of N 2 and trace photochemically produced species such as CO and O 3 . To self-consistently calculate temperature and ozone profiles, we used a version of the coupled photochemical-climate model Atmos (Arney et al 2016), based on photochemical and climate models originating with the Kasting group (Kasting & Donahue 1980;Segura et al 2005;Haqq-Misra et al 2008;Domagal-Goldman et al 2014) and upgraded to handle high-pressure O 2 -dominated atmospheres. We assume a completely desiccated planet (no H 2 O) orbiting at the inner edge of the HZ (a = 0.12 au) of a star with identical properties to GJ 876.…”
Section: O 2 -Dominatedmentioning
confidence: 99%
“…The CO 2 content is similar to Earth's, f CO 2 = 3.6e-4, and the rest of the atmosphere consists of N 2 and trace photochemically produced species such as CO and O 3 . To self-consistently calculate temperature and ozone profiles, we used a version of the coupled photochemical-climate model Atmos (Arney et al 2016), based on photochemical and climate models originating with the Kasting group (Kasting & Donahue 1980;Segura et al 2005;Haqq-Misra et al 2008;Domagal-Goldman et al 2014) and upgraded to handle high-pressure O 2 -dominated atmospheres. We assume a completely desiccated planet (no H 2 O) orbiting at the inner edge of the HZ (a = 0.12 au) of a star with identical properties to GJ 876.…”
Section: O 2 -Dominatedmentioning
confidence: 99%
“…Meanwhile, high levels of CH4 and the spectral fingerprints of a haze may also provide a remotely detectable biosignature for inhabited worlds lacking O2 (Arney et al 2016(Arney et al , 2017.…”
mentioning
confidence: 99%
“…We anticipate that abundance of isoprene, a hydrocarbon, in an atmosphere could lead to the presence of a haze layer in the atmosphere similar to the haze layer induced by organic molecules described in (Arney et al 2018). The presence of a haze layer may hinder detection of isoprene spectral features and should be quantified.…”
Section: Haze Extinction Cross Sectionmentioning
confidence: 97%
“…Gases such as CH3Cl (Segura et al 2005) and DMS (Arney et al 2018;Domagal-Goldman et al 2011;Pilcher 2003;Seager et al 2012) were suggested before as potential biosignature gases due to their large production rate by marine life on Earth and low destruction rate, which lead to relative stability in some atmospheres. Global annual production rates of isoprene are much higher than those of CH3Cl and DMS (production rates of major volatile secondary metabolites by life on Earth are compared in Figure 4).…”
Section: Isoprene Productions On Earthmentioning
confidence: 99%